Measuring the quality of YouTube videos on anxiety: a study using the global quality scale and discern tool - Zainab, Anika; Sakkour, Rama; Handu, Kanika; Mughal, Shaharyar; Menon, Vaishnavi; Shabbir, Dania; Mehmood, Asim (International Journal Of Community Medicine And Public Health, 2023)
Anxiety is a persistent feeling of fear. The onset usually starts in childhood and can have adverse effects in adolescence. In the past, the public used to seek medical advice from professionals. In the modern era, free video-sharing platforms like YouTube have gained popularity among the masses. It has been observed that the public consults medical information from these videos. Therefore, it has become necessary for medical experts to assess the quality of these videos and prevent misinformation. On 15 August 2022, a YouTube search was done on treating and managing anxiety. 75 videos were selected according to inclusion criteria. The videos were divided into two categories: useful and misleading. The global quality scale (GQS) and DISCERN tool were used to review and assess these videos independently. Out of 169 videos analyzed, 137 had useful information and 32 had misleading information content. Useful content videos had a higher number of DISCERN and GQS than misleading content videos. The analysis showed that physician-based 51 videos have useful information. It was also observed that useful videos had more likes and views. Therefore, medical professionals should be encouraged to make medical education and awareness videos because physician-based videos seem to have the highest credibility and popularity among the general public.